Is contextual animation needed in multimedia learning games for children? An eye tracker study. (5th October 2020) - Javora, Ondřej; Hannemann, Tereza; Volná, Kristina; Děchtěrenko, Filip; Tetourová, Tereza; Stárková, Tereza; Brom, Cyril
Abstract: The present study investigates affective‐motivational, attention, and learning effects of unexplored emotional design manipulation: Contextual animation (animation of contextual elements) in multimedia learning game (MLGs) for children. Participants ( N = 134; M age = 9.25; Grades 3 and 4) learned either from an experimental version of the MLG with a high amount of contextual animation or from an identical MLG with no contextual animation (control). Children strongly preferred ( χ 2 = 87.04, p  < .001) and found the experimental version more attractive ( p  < .001, d = −1.11). No significant differences in overall enjoyment and learning outcomes were found. Attention differences, measured by dwell times and fixation durations, were small and reached only borderline significance ( p = .035; d = −0.39). The implication is that contextual animation in MLG for children increases such instructional materials' attractiveness without compromising cognitive processes needed for learning; however, it does not lead to their higher instructional efficiency. Lay Description: What is already known about this topic: Contextual animation is frequently used in multimedia learning games (MLGs) for children. Contextual animation is understood to be non‐expository picture motion, which can be added to already existing representational pictures that provide context for target instruction. It is not known whether or not contextual animation, which embellishes already existing representational contextual pictures, harms learning for children in the case of MLGs. What this paper adds: Children (Grades 3 and 4) strongly prefer the game with added contextual animation compared to the game without it. No between‐group differences in overall learning enjoyment and learning outcomes were found. Small attention‐allocation effects of borderline significance were detected. Implications for practice Adding contextual animation (i.e., added non‐expository picture motion) to multimedia learning games for children will increase the attractiveness of the materials and will not hamper learning. Investment into the production of costly contextual animation may be worthwhile in the case of instructional games intended for uncontrolled settings (e.g., at home or during leisure time). In formal contexts (e.g., school), it is less clear whether investment into contextual animation is needed, since children are extraneously motivated to learn and animation does not appear to enhance learning outcomes.